EXPERIMENTAL INVESTIGATION OF SULPHUR ISOTOPIC FRACTIONATION BETWEEN DISSOLVED AND GASEOUS H2S - Szaran J. (My University, 1996)
In this study sulphur isotope fractionation between undissociated dissolved H2S and H2S gas has been investigated experimentally. Such measurements were carried out at temperatures of 11o, 20o and 30oC. The experiment was performed at pH = 5, at which H2S remains nearly totally undissociated.The experimental conditions were as follows: (1) an aliquot of distilled water was saturated with H2S at a pressure of 1 atm; (2) the system containing gaseous and dissolved H2S was kept at constant temperature for a certain time; and (3) the gas phase was separated from the solution prior to sulphur extraction from both phases, which was prepared in the form of SO2 gas for isotopic analysis.The results obtained show that dissolved undissociated H2S is enriched in the heavy isotope with respect to gaseous hydrogen sulphide in the temperature range 11-30oC. In this temperature range the permil fractionation obeys the following formula:Δ 34S = + (2.75 +/- 0.15) - (56 +/- 7) . 10-3t (oC)The fractionation factor, α, can be calculated from the following expression:α = 1 + 0.001Δ 34S